Proposal for Open Standard Based Legal Document Management System for the Parliament of Bangladesh - Murad, Mohammad Hasan; Islam, Mohammad Saidul (Richtmann Publishing, 2012)
Purpose : A fast and progressive legislative system is necessary for Bangladesh in order to address pressing issuewhere regulatory solutions are required. In order to achieve efficiency and functionality of the working of the legislative body,information systems should be introduced for reliable creation, storage, retrieval and dissemination of legislative documents suchas bills, discussions, committee reports ,arguments ,minutes of parliament and laws. In this paper We have explored themethods and challenges of developing a legislative Document Management System (DMS) for the Bangladesh Parliament.Approach – This research outlines the need for a Document Management System for the Bangladesh Parliament and proposesstrategies that can be followed in building process of such system especially in connection with the structuring of documents andfollowing open standard. Findings – It can be concluded that A Document Management System based on XML standard will beideal for the Bangladesh Parliament despite challenges and obstacles. Limitation: This paper does not cover the technical sideof the DMS. It is out of the scope of the paper to discuss all components of a Legislative Information System. Further researchmay be conducted on developing specific models of the Information System for the Parliament. Value – This paper has thepotentials to inspire the e-government proponents of the developing countries to promote ICT in the Legislative Houses and willact as a primary guideline for the policy makers.